The birth of solidarity the history of the French welfare state - Ewald, François (Duke University Press, 2020)
"THE BIRTH OF SOLIDARITY traces the emergence of social welfare legislation through debates about workplace accidents in France. François Ewald shows that with industrialization in the 19th century, workplace accidents became increasingly frequent and complex, and the rise of statistics and insurance shifted ideas about who should be held responsible. Whereas early commentators claimed workers and their patrons were responsible for the consequences of workplace accidents, by 1898 the French government declared that workplace accidents needed to be covered by a state-regulated social security policy. This shift in approach marked the emergence of the modern French welfare state. The book is divided into three parts. In the first, Ewald looks at the 1841 law governing child labor in factories and 1830s court cases concerning workplace accidents to show how these industrial regulations challenged the earlier liberal philosophies involving a social contract, which had assumed individual benevolence as the basis for all social assistance. In contrast, new forms of patronage emerging in the 1840s required French employers to provide compensation for their workers, including pensions, education, and company stores. The second part considers the development of insurance as an outgrowth of the philosophy of Adolphe Quételet, who applied probabilistic calculus to social phenomena, like risk. Ewald shows that insurance gave workers a way to save for the future and the wealthy a guarantee against accidents. The third part looks at legislators' increased focus on social solidarity rather than individual responsibility in the latter half of the 19th century, with the 1898 labor law solidifying the government's role as a regulator acting on behalf of workers, and insurance agents' role in assessing fault and responsibility. Ewald, who had been a Maoist activist during the French student uprising of May 1968, became Michel Foucault's doctoral student and assistant in the 1970s. When Foucault's partner Daniel Defert was commissioned by the French Labour Ministry to do a series of studies on the history of workplace accidents, Defert enlisted Ewald, along with a number of Foucault's other students, to conduct the research. This research eventually formed the basis of Ewald's dissertation and first book, Histoire de l'Etat providence: Les Origines de la solidarité, originally published in 1986, revised in 1996, and now translated into English for the first time, with a critical introduction by Melinda Cooper that discusses Ewald's later career as a state bureaucrat and consultant for industry. THE BIRTH OF SOLIDARITY will interest students and scholars of political theory, Marxism, social theory, and French history"--